THE USAGE OF THE LAW OF REQUISITE VARIETY IN MANAGEMENT OF EDUCATIONAL PROCESS - TSYMBAL, Oksana (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Nowadays education aimed at training of future specialists for their professional career. According to the systematic educational approach, education is a complete system consisting of interrelated elements that form a particular set. Purpose lies in the reasoning of the Ashby’s Law relevance in the educational management and in the identifying of the ways of increasing its effectiveness. Results. The article investigates the question of educational process management based on the systematic approach using cybernetic law. The author tried to apply the Ashby’s Law for the realization of the methods of educational management and the estimation of their efficiency and prospects. According to Ashby’s Law, the system of educational process management is in its harmonized state and is effective, when the variety of the managed subsystem is less than the variety of the managing one. Such a state is shifty, that is why one can find four methods to reach it: 1) to limit variability of the managed system (clear limits of development, there can be no more and no less variants than those given by the managing system, creativeness and initiativeness have no place to develop, studying process is reproductive); 2) to organizationally and meaningfully simplify the systems or decrease the level of requirements to the educational management (reduction of number of the constantly controlled and managed features of the subsystem which is managed by a higher subsystem); 3) to increase the level of variety of administrative structures (to artificially increase its number) or increase the forms, methods and technologies of management (in that case a formal lack of such methods takes place); 4) to self-organize the management objects through limitation of the controlled features creating self-regulated and self-managed subsystems or elements. We consider the transmission of some administrative functions from a teacher to a student to be the most effective way that is relevant to the nowadays level of educational system. Conclusion. The Law of Requisite Variety can be applied in the educational system for determination of an optimal correlation of variety of both the managing and managed subsystems.